LATENT CONFLICT POSSIBILITIES OF MINORITIES UNDER THE SHARIA LAW - Manan, Abdul; Salasiyah, Cut Intan; Fadhilah, Muhammad Arif; Muhibbuthabry, Muhibbuthabry; AS, Nasruddin; Embong, Rahimah; Rizki, Syukri (Islam Futura, 2025)
Aceh has authoritative legal privilege as it has a special autonomy in implementing sharia as the legal law. In the Islamic tenet, as the foundation of the Islamic law, harmony in society is one of the purposes of implementing sharia. Yet, upon the implementation of sharia in Aceh, several cases of violation interfered with the unity of people with different beliefs in Aceh. This study examined the issue of the scorching church in Singkil to portray intolerance from various perspectives. A qualitative approach utilizing an ethnographic study is implemented with observation and interviews of 25 respondents selected by purposive sampling. The result indicated that misunderstanding led by unharmonious communication and political influence triggered the religious-based conflict in Singkil. Mutual understanding through dialogue and rejuvenating local culture and wisdom are ways to build and maintain harmony among people with different beliefs upon implementing sharia in Aceh.Aceh has authoritative legal privilege as it has a special autonomy in implementing sharia as the legal law. In the Islamic tenet, as the foundation of the Islamic law, harmony in society is one of the purposes of implementing sharia. Yet, upon the implementation of sharia in Aceh, several cases of violation interfered with the unity of people with different beliefs in Aceh. This study examined the issue of the scorching church in Singkil to portray intolerance from various perspectives. A qualitative approach utilizing an ethnographic study is implemented with observation and interviews of 25 respondents selected by purposive sampling. The result indicated that misunderstanding led by unharmonious communication and political influence triggered the religious-based conflict in Singkil. Mutual understanding through dialogue and rejuvenating local culture and wisdom are ways to build and maintain harmony among people with different beliefs upon implementing sharia in Aceh.